Effects of Irrigation at Different Fractions of Crop Evapotranspiration on Water Productivity and Flavonoid Composition of Cabernet Sauvignon Grapevine - Torres, Nazareth; Yu, Runze; Martínez-Lüscher, Johann; Kostaki, Evmorfia; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2021)
Climate change models predict lower precipitation and higher air temperatures that will negatively affect viticultural regions. Irrigation of vineyards will be crucial for mitigating abiotic stress during the growing season. However, the environmental impact of irrigation requires consideration for ensuring its sustainability in the future. We evaluated the standard irrigation practices on grapevine water use efficiency, berry flavonoid composition, vineyard water footprint, and Arbuscular Mycorrhizal Fungi-grapevine symbiosis in two seasons with contrasting amounts of precipitation. The irrigation treatments consisted of weekly replacement of 25%, 50% and 100% of crop evapotranspiration (ETc) during two growing. Irrigation in grapevine vineyards mitigated the water scarcity when precipitation during the dormant season was not sufficient. The results provided field data supporting that despite the low rainfall recorded in one of the seasons, increasing the amount of irrigation was not advised, and replacing 50% ETc was sufficient. In this treatment, berry composition was improved with increased contents of TSS, anthocyanins and flavonols, and a stable flavonoid profile without an economic decrease in yield. In addition, with 50% ETc the mycorrhizal symbiosis was not compromised and water resources were not highly impacted. Altogether, our results provide fundamental knowledge for viticulturists to design an appropriate irrigation schedule under the future warming scenarios with .